Selected Decisions, 19th Ed. 1994. (Selected Decisions, 1994)
This paper discusses several IMF's selected decisions of the Executive Board and selected documents. The procedures set forth in Section IV of SM/77/277 are approved, and members shall be guided by the considerations in Section IV with respect to the prompt notification of any changes in their exchange arrangements. Once the procedures for initial notification have been clarified, only a few issues remain to be dealt with in respect of subsequent notifications. One of these is the question of what would constitute a change in an exchange arrangement requiring notification. Upon receipt of notification of a change in exchange arrangements from a member the IMF staff would circulate it to the Executive Board. If the Board wishes, it could continue to be the normal practice that whenever a change is significant, its communication to the Board would be followed promptly by a staff paper describing the context of the change in policy and giving the IMF staff's assessment.